БЎЛАЖАК ЎҚИТУВЧИНИНГ ШАХС БЎЛИБ ШАКЛЛАНИШИДА КОММУНИКАТИВ ҚОБИЛИЯТНИНГ МОҲИЯТИ (Scientific journal of the Fergana State University, 2023)
This article deals with the role and place of communicative skills in formation of future teachers. It may use by future specialists who dealing with the developing problems communicative capabilities